257 Sodium-glucose CO-transporter-2 inhibitors eligibility in patients with heart failure with reduced ejection fraction. (8th December 2021) - Ferrari, Ilaria; Cicogna, Francesco; Tota, Claudia; Calò, Leonardo; Monzo, Luca
Abstract: Aims: The sodium–glucose co-transporter-2 (SGLT2) inhibitors dapagliflozin and empagliflozin have been demonstrated to reduce adverse cardiovascular outcomes in patients with heart failure with reduced ejection fraction (HFrEF). Limited data are available characterizing the generalizability of SGLT2 inhibitors treatment in the clinical practice. The aim of the study was to evaluate the proportion of outpatients with HFrEF that would be eligible for SGLT2 inhibitors in a contemporary real-world population. Methods and results: We retrospectively evaluated patients with chronic stable HFrEF followed-up at the HF outpatient clinic of our institution. Patients' eligibility was assessed according to the entry criteria of DAPA-HF (dapagliflozin) and EMPEROR-Reduced (empagliflozin) trials and to US Food and Drug Administration (FDA) label criteria (only dapagliflozin). A total of 441 HFrEF patients was enrolled. According to the major inclusion and exclusion criteria from DAPA-HF and EMPEROR-Reduced trials, 198 (45%) patients would be candidates for initiation of both dapagliflozin and empagliflozin, 61 (14%) would be eligible only to dapagliflozin and 23 (5%) only to empagliflozin, without significant differences between diabetic and non-diabetic patients ( P = 0.23). Among patients not suitable for gliflozins treatment (159 patients; 36%), the major determinant of ineligibility was the failure to achieve the predefined NT-proBNP inclusion threshold. Excluding NTproBNP as per FDA label criteria, dapagliflozin eligibility increased to 86%. Conclusions: In our real-world analysis a large proportion of HFrEF patients would be candidates for initiation of SGLT2 inhibitors, supporting its broad generalizability in clinical practice. This would be expected to reduce morbidity and mortality in eligible patients.